ANALISIS PELAKSANAAN PROGRAM PENANGGULANGAN DEMAM BERDARAH DENGUE (DBD) DI PUSKESMAS PINELENG KABUPATEN MINAHASA - Wongkar, Yudi Emili; Langitan, Fentje; Telew, Agusteivie (Yayasan Syalom Cipta Sumikolah, 2024)
Dengue is a viral infectious disease that is transmitted through mosquitoes and is a public health problem in the world (World Health Organization, 2021). Data from the North Sulawesi Central Statistics Agency (BPS), the morbidity rate for dengue fever per 100,000 population in 2020-2021 is 42.8. In Minahasa Regency the incidence of dengue fever in 2020 was 58.1 and increased to 58.2 in 2021. According to the 2021 Minahasa District Health Service Government Agency Performance Report (LKjIP), the incidence of dengue fever in 2018 increased significantly to 307 cases (0 .91%), very high compared to previous years. The increase in 2019 was 629 cases (1.84%). In 2020, 205 cases (0.59%) were detected. The aim of this research is to find out how to analyze the implementation of the dengue hemorrhagic fever (DBD) control program at the Pineleng Community Health Center, Minahasa Regency. The method used is a descriptive qualitative approach. The results of the research show that the dengue fever prevention program at the Pineleng Community Health Center was implemented well in terms of human resources, funds, counseling and activities. However, the equipment used for fogging is still borrowed from the Health Service or other Community Health Centers, and for epidemiological investigations, sometimes when there are many cases where there is a shortage of health workers. In conclusion, the Pineleng Community Health Center should be able to increase the availability of facilities and infrastructure and maximize health workers.